2002
DOI: 10.2172/803723
|View full text |Cite
|
Sign up to set email alerts
|

Fuel-Flexible Gasification-Combustion Technology for Production of H2 and Sequestration-Ready Co2

Abstract: It is expected that in the 21 st century the Nation will continue to rely on fossil fuels for electricity, transportation, and chemicals. It will be necessary to improve both the thermodynamic efficiency and environmental impact performance of fossil fuel utilization. General Electric Energy and Environmental Research Corporation (GE EER) has developed an innovative fuel-flexible Advanced Gasification-Combustion (AGC) concept to produce H 2 and sequestration-ready CO 2 from solid fuels. The AGC module offers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Experiments conducted in the labatory -scale reactor further suggested that a high calcium sorbent to coal ratio ( ∼ 16:1 by weight) was required to avoid CO 2 emission from the reactor. 32 The experimental results also suggest that a 4:1 ratio by weight of calcium sorbent to Fe 2 O 3 enhances H 2 production. 32 A further increase in Fe 2 O 3 , however, will lead to a reduction in H 2 yield.…”
Section: Gasifi Er Testmentioning
confidence: 78%
See 2 more Smart Citations
“…Experiments conducted in the labatory -scale reactor further suggested that a high calcium sorbent to coal ratio ( ∼ 16:1 by weight) was required to avoid CO 2 emission from the reactor. 32 The experimental results also suggest that a 4:1 ratio by weight of calcium sorbent to Fe 2 O 3 enhances H 2 production. 32 A further increase in Fe 2 O 3 , however, will lead to a reduction in H 2 yield.…”
Section: Gasifi Er Testmentioning
confidence: 78%
“…As shown in Figure 5.10 , which previously was shown as Figure 1.27 , the Fuel -Flexible AGC Process consists of three interconnected fl uidized -bed reactors. 30 In the fi rst reactor, or the gasifi er, coal partially is gasifi ed with steam to form a mixture of H 2 , CO and CO 2 . The CO 2 generated during the coal gasifi cation is captured in situ by CaO under operating conditions of 750 ° C -850 ° C and 17 -20 atm.…”
Section: Fuel -Flexible Advanced Gasifi Cation -Combustion Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The GE Process obtains a hydrogen concentration of only 80%. 61 The calcium -based chemical looping process mentioned is discussed in detail in Chapter 5 .…”
Section: Calcium Looping Process Using Gaseous Fuelsmentioning
confidence: 99%
“…61.1% CO,35.1% H 2 , and 3.8% CO 2 (mol%) is sent to the bottom of the reactor at a rate of 1,686 mL/min (STP, Standard Temperature and Pressure). The gas composition is chosen to be similar to the syngas generated from a Shell SCGP gasifi er.…”
mentioning
confidence: 99%